Preparation and properties of recombinant Clostridium ramosum IgA proteinase. Isolation of Fc-SC and Fab fragments of human secretory IgA - Krupka, Michal; Raskova Kafkova, Leona; Barkocziova, Lucia; Sloupenska, Kristyna; Brokesova, Diana; Sebela, Marek; Raska, Milan (Protein expression and purification, 2021)
Immunoglobulin A (IgA) proteinase from Clostridium ramosum is the enzyme which cleaves IgA of both subclasses; in contrast, the other bacterial proteinases cleave only IgA1 proteins. Previous reports characterized the activity of proteinase naturally secreted by C. ramosum specific for the normal human serum IgA of IgA1 and IgA2m(1) subclasses and also for secretory IgA (SIgA). Its amino acid sequence was determined, and the recombinant proteinase which cleaved IgA of both subclasses was prepared. Here we report the optimized expression, purification, storage conditions and activity testing against purified human milk SIgA. The recombinant C. ramosum IgA proteinase isolated in the high degree of purity exhibited almost complete cleavage of SIgA of both subclasses. The proteinase remained active upon storage for more than 10 month at -20 °C without substantial loss of enzymatic activity. Purified SIgA fragments are suitable for studies of all antigen-binding and Fc-dependent functions of SIgA involved in the protection against infections with mucosal pathogens.
Keywords: bakteriální proteiny; Recombinant Proteins; Peptide Hydrolases; imunoglobulin A sekreční; Immunoglobulin Fab Fragments; lidé; Bacterial Proteins; imunoglobuliny - Fab fragmenty; rekombinantní proteiny; Immunoglobulin A, Secretory; imunoglobuliny - Fc fragmenty; Immunoglobulin Fc Fragments; Humans; Firmicutes; proteasy